Current trends in horse stall design for equine housing: a case study of commercial centers in peninsular Malaysia - Nur Fadilah Darmansah; Azilah Baddiri; Mohd Saidin Misnan; Ahmad Azeem Ahmad Astor (IDEAS, 2024)
Horse stall design plays a vital role for every horse owner and equine center. In early planning stage, it is crucial to decide the factors that may affect the design of the horse stall as poor construction stall which reduces horse performance. Hence, it raises number of injury cases and lower the horses confident. The objective this study is to investigate the current design component of commercial equine center. The chosen five (5) commercial equine centers are well-known equine center with criteria including active operating livery services and frequent conducting equestrian competition. Data collection using the checklist in observation to six (6) main component which are dimension, door, ventilation and lighting, partition, interior (watering and feeding) flooring, and drainage. The results of study shown that the stall dimension typically used in commercial equine centers is 12 x 12 ft in stall size, 7 ft in wall height, and 15 ft in ceiling height. Galvanized iron material for door, approximately 5 ft and 6 ft door width, 4 ft door height, placing the door on the left of the horse stall with door hinges and bolt were used. The air circulation fan and natural ventilation as well as electric light fixtures and natural lighting from outside. Combination of brick or concrete with metal for partition material for stall at height of 7ft or 8 ft. Heavy-duty yellow plastic for water and feed were used and placed front side of stall. The flooring are used concrete with cement along with rubber matt for absorption. Overall, the current stall design trends for equine housing in commercial centers in Peninsular Malaysia prioritize enhancing the well-being and performance of horses. The key characteristics of these trends involve roomy and well-ventilated stalls, high quality construction materials, and features that enhance natural light and airflow. Moreover, there is an increasing focus on ergonomic design features intended to improve horse comfort and minimize the likelihood of damage. These patterns highlight the changing comprehension and emphasis on equine welfare among facility managers and owners in Malaysia's equine industry.